The Landscape of Featured Metabolism-Related Genes and Imbalanced Immune Cell Subsets in Sepsis - She, Han; Tan, Lei; Zhou, Yuanqun; Zhu, Yu; Ma, Chunhua; Wu, Yue; Du, Yuanlin; Liu, Liangming; Hu, Yi; Mao, Qingxiang; Li, Tao (Frontiers in Genetics, 2022)
Sepsis is a heterogeneous disease state triggered by an uncontrolled inflammatory host response with high mortality and morbidity in severely ill patients. Unfortunately, the treatment effectiveness varies among sepsis patients and the underlying mechanisms have yet to be elucidated. The present aim is to explore featured metabolism-related genes that may become the biomarkers in patients with sepsis. In this study, differentially expressed genes (DEGs) between sepsis and non-sepsis in whole blood samples were identified using two previously published datasets (GSE95233 and GSE54514). A total of 66 common DEGs were determined, including 52 upregulated and 14 downregulated DEGs. The Gene Set Enrichment Analysis (GSEA) results indicated that these DEGs participated in the several metabolic processes including carbohydrate derivative, lipid, organic acid synthesis oxidation reduction, and small molecule biosynthesis in patients with sepsis. Subsequently, a total of 8 hub genes were screened in the module with the highest score from the Cytoscape plugin cytoHubba. Further study showed that these hub DEGs maybe robust markers for sepsis with high area under receiver operating characteristic curve (AUROC). The diagnostic values of these hub genes were further validated in myocardial tissues of septic rats and normal control by untargeted metabolomics analysis using liquid chromatography-mass spectrometry (LC-MS). Immune cell infiltration analysis revealed that different infiltration patterns were mainly characterized by B cells, T cells, NK cells, monocytes, macrophages, dendritics, eosinophils and neutrophils between sepsis patient and normal control. This study indicates that metabolic hub genes maybe hopeful biomarkers for prognosis prediction and precise treatment in sepsis patients.